ANALISIS STRATEGI BLUE OCEAN “CHINA CONSTRUCTION BANK INDONESIA” - Witjaksono, Cindy Julian (FEB Universitas Sam Ratulangi Manado, 2023)
This research aims to analyze the blue ocean strategy of the Company